Visualization of the Values of the AL Anwar Islamic Boarding School to Improve the Personal Qualities of Santri - Kurli, Anis; Hidayat, Hidayat; Hidayat, Imam; Zarnuji, Zarnuji; Norrahman, Rico (Jurusan Ilmu Komunikasi UTM, 2024)
The Industrial Revolution has changed the values of Islamic Boarding Schools which have begun to fade among students as the nation's next generation. Santri are more busy with their social media than living socially with the community in teaching and exemplifying the characteristic educational values they receive at Islamic boarding schools. In fact, the values of Islamic boarding school education have not been a reflection of improving the quality of students in society. The theory used in this research to instill Islamic boarding school values in students is visualization through documentary videos as a learning medium, so that students can easily access and remember them in everyday life. The results of this research show that there is a change in the behavior of santri in an effort to improve personal quality, namely that the santri are more motivated to learn and are happy to do good as a reflection of the santri as role models for their community. The improvement in personal quality in question is related to increasing the moral quality and knowledge of students. The true philosophy of santri is the continuation of the struggle of teachers and ulama' to guide society in religious knowledge and face increasingly competitive life